A Scientific view and analysis of theatre art Yakshagana - Gopalkrishna Hegde; Gautam Hegde (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2022)
Many of the Indian performing arts have deep scientific/engineering aspects involved in them without being recognised or studied. Yakshagana is one of such arts being performed in coastal districts of Karnataka and has a history of more than 500 years. Yakshagana is a team, multidisciplinary art involving classical music, percussions, dance, dialogue, comedy, costumes, and scholarly discussions. This article discusses the components/parameters of the Yakshagana art form from a scientific and engineering perspective, and we have attempted to formulate mathematical equations for a better understanding of the art execution, artistâ€™s capacity and overall performance. Empirical mathematical relations are formulated to estimate the performance index to grade the quality of the overall performance of the day. As art is an â€œall-in-oneâ€ form of art performance, it is represented using a Venn diagram. Four main components of Yakshagana and the importance of the coordination between them for successful, cohesive and high-quality performance are analysed by incorporating scientific and engineering approaches. We hope that the present study will open up further scientific research on long-duration performing Indian traditional art forms